Efeito da administração intravenosa repetida de lidocaína associada à pregabalina em pacientes fibromiálgicas: evidências sobre o estresse oxidativo - Nogueira, José Barreto Cruz (2019)
Fibromyalgia (FM) is a chronic and painful syndrome, with a negative biopsychosocial impact on patients' quality of life. The presence of oxidative stress (EO) may represent one of the possible causes of the syndrome and the possibility of the existence of biomarkers capable of elucidating the diagnosis, making objective the evaluation of the pain. Objective: To evaluate the effects of lidocaine and pregabalin on EO: glutathione (GSH), malonaldialdehyde (TBARS), antioxidant power by iron reduction (FRAP), sulfhydryl, superoxide dismutase (SOD) and catalase). Methods: Clinical trial approved by the Ethics and Research Committee with Human Beings of the Federal University of Sergipe (UFS), on 05/07/2018. They were included in the study by signing the Informed Consent Term (TCLE). Healthy women and women diagnosed with fibromyalgia were initially divided into two groups, the control group being composed of women without FM and the pregabalin group by women with FM. After the first collection, the pregabalin group was subdivided and randomized into two subgroups, the pregabalin (GP) group composed of women who received 0.9% sodium chloride solution and the pregabalin and lidocaine group (LPG) represented by women treated with pregabalin and who received intravenous lidocaine given repeatedly for five weeks. The control group (CG) responded only to the pharmaceutical care questionnaire (QAF) at the initial time (Ti) while the other 25 women answered the four forms: QAF; Visual Analog Scale (EVA); Impact of Fibromyalgia (FIQ) and Neuropathic Pain (DN4) proposed in two moments: Ti and Tf (final time). The clinical protocol of the fibromyalgic patients was developed with the evaluation in five moments, through the application of all the questionnaires. The laboratory protocol was divided into two moments of blood collection: starting before the first infusion (Ti) and after the last infusion (Tf), to compare the OE parameters between the control group and the pregabalin group. Ten (10) women in the CG and twenty-five (25) in the GP, later subdivided into two groups (GP, GPL) were allocated. At the end of the study the GP was composed of 10 women and the LPG by 15 women. Regarding the intensity of resting pain (VAS), there was a significant reduction in LPG (p <0.0002) between Ti times (8.33 ± 1.0) and Tf (4.89 ± 1.05), not (p <0.061) between Ti times (7.71 ± 1.1) and Tf (6.13 ± 2.17). Comparison of the oxidative stress parameters of GSH, TBARS, FRAP, sulfhydryl, SOD and CAT between the GC and GP groups showed lower values of GSH (p <0.001) and CAT (p <0.01), TBARS presented higher levels in fibromyalgia. When comparing intergroups (GP and LPG), the levels of GSH, TBARS and FRAP were statistically significant in the pregabalin / lidocaine group (p <0.01), comparing before and after lidocaine infusion. Conclusion: A possible synergistic effect was identified in the association between venous lidocaine and pregabalin in fibromyalgic women, as observed by EO parameter values and through improvement in the clinical pain scores and the functionality of the patients involved.